1985
DOI: 10.1192/bjp.147.6.647
|View full text |Cite
|
Sign up to set email alerts
|

Puerperal Mental Illness, Clinical Features and Classification: A Study of 142 Mother-and-Baby Admissions

Abstract: The case notes were studied of 142 mothers admitted to psychiatric hospitals in the south-east Thames region within 12 months of childbirth during the years 1979 and 1980. Only 6% of the sample were categorised as schizophrenics by RDC criteria, whereas affective disorders were found to predominate in 80%. Manic and schizo-affective illnesses almost always began within two weeks of parturition, as did psychotic depressions. A third of the patient sample had suffered relatively minor disorders, and given adequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
42
2
4

Year Published

1993
1993
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(55 citation statements)
references
References 19 publications
7
42
2
4
Order By: Relevance
“…This finding was also in line with the study by Meltzer and Kumar [16]. It has already been reported in earlier prospective studies [21][22][23] and in a recent Swedish community-based study [Bågedahl-Strindlund and Monsen Börjesson, unpubl.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding was also in line with the study by Meltzer and Kumar [16]. It has already been reported in earlier prospective studies [21][22][23] and in a recent Swedish community-based study [Bågedahl-Strindlund and Monsen Börjesson, unpubl.…”
Section: Discussionsupporting
confidence: 82%
“…In agreement with Meltzer and Kumar's [16] study, presenting in-patients with puerperal mental illness in England, we found that women with schizophrenic symptoms remained the longest time in hospital at index admission.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The illnesses that can manifest with psychosis in the postpartum period include major depression with psychotic features, bipolar I, bipolar II, schizoaffective, unspecified functional psychosis, and brief psychotic disorder. Studies since the 1980s have linked the occurrence of postpartum psychosis to underlying bipolar disorder diagnosis in over 80 % of patients (Meltzer and Kumar 1985;Kendell et al 1987;Brockington et al 1981). Bipolar disorder is widely accepted as the illness underlying most cases of postpartum psychosis.…”
Section: Postpartum Psychosismentioning
confidence: 99%
“…zykloides Symptombild, während Frauen mit einem späteren Krankheitsbeginn häufiger paranoid sind [20]. Eine Betrachtung der "Postpartumpsychosen" unter dem Konzept der Kraepelinschen Dichotomie schizophrener vs. affektiver Psychosen spricht stark für eine überwiegend affektive Natur dieser Psychosen [21,11,12,[22][23][24][25]. Das syndromale Gepräge speziell der früh sich manifestierenden Postpartumpsychosen legt eine Verbindung zum Konzept der zykloiden Psychose nahe [26,27].…”
Section: Klinische Phänomenologie Der Postpartalen Psychosenunclassified